Molecular Insight into Long‐Wavelength Fluorogenic Dye Design: Hydrogen Bond Induces Activation of a Dormant Acceptor. Issue 51 (3rd November 2015) - Kisin‐Finfer, Einat; Redy‐Keisar, Orit; Roth, Michal; Ben‐Eliyahu, Ronen; Shabat, Doron
Abstract: The detection of chemical or biological analytes in response to molecular changes relies increasingly on fluorescence methods. Therefore, there is a substantial need for the development of improved fluorogenic dyes. In this study, we demonstrated how an intramolecular hydrogen bond activates a dormant acceptor through a charge induction between phenolic hydrogen and a heteroaryl nitrogen moiety. As a result, a new fluorochrome is produced, and the molecule exhibits a strong fluorescent emission. When the strength of the hydrogen bonding was increased by conformational locking, the obtained dye emitted at longer wavelengths and fluoresced under physiological conditions. The dye was implemented in a turn‐ON system responsive to hydrogen peroxide. The molecular insight provided by this study should assist in the design of fluorescent dyes that are suitable for in vitro and in vivo applications. Abstract : An intramolecular hydrogen bond activates a dormant acceptor through a charge induction between phenolic hydrogen and a heteroaryl nitrogen moiety. As a result, a new fluorochrome is produced, and the molecule exhibits a strong fluorescent emission. The dye was implemented in a turn‐ON system responsive to hydrogen peroxide.